OUTREACH: phase 2 study of lisocabtagene maraleucel as outpatient or inpatient treatment at community sites for R/R LBCL - Yuliya Linhares; Cesar O. Freytes; Mohamad Cherry; Carlos Bachier; Michael Maris; Daanish Hoda; Juan C. Varela; Courtney Bellomo; Scott Cross; James Essell; Suzanne Fanning; Howard Terebelo; et al. (Blood Advances)
Abstract: Lisocabtagene maraleucel (liso-cel) is an autologous, CD19-directed, 4-1BB chimeric antigen receptor (CAR) T-cell product approved for relapsed/refractory (R/R) large B-cell lymphoma (LBCL). We present the OUTREACH primary analysis, evaluating the safety and efficacy of outpatient monitoring after liso-cel treatment at community sites in the United States. Adults with R/R LBCL after ≥2 prior lines of therapy received liso-cel. Outpatient vs inpatient monitoring was per investigator discretion. The primary end points were incidences of grade ≥3 cytokine release syndrome (CRS), neurological events (NEs), prolonged cytopenia, and infections. Efficacy was a secondary end point. Eighty-two patients received liso-cel (outpatient monitored, 70%; inpatient monitored, 30%). The median follow-up was 10.6 months (range, 1.0-24.5). In outpatients and inpatients, grade ≥3 CRS occurred in 0% and 0%, NEs in 12% and 4%, infections in 12% and 8%, and prolonged cytopenia in 33% and 32%, respectively. Among outpatients, 25% were never hospitalized after infusion, and 32% were hospitalized ≤72 hours after the day of infusion; the median time to hospitalization was 5.0 days (range, 2-310). The median initial hospitalization duration after liso-cel was 6.0 days (range, 1-28) for outpatients and 15.0 days (range, 3-31) for inpatients. Objective response rate was 80%, complete response rate was 54%, and the median duration of response was 14.75 months (95% confidence interval, 5.0 to not reached). OUTREACH is, to our knowledge, the first and largest study to prospectively assess CAR T-cell therapy with outpatient monitoring in community-based medical centers. Liso-cel demonstrated meaningful efficacy with favorable safety in patients with R/R LBCL. Data support the feasibility of liso-cel administration at community sites with outpatient monitoring. This trial was registered at www.ClinicalTrials.gov as #NCT03744676.